Soldier Sahibs the men who made the North-West Frontier - Allen, Charles (Abacus, 2000)
SOLDIER SAHIBS is the astonishing story of a brotherhood of young men who together laid claim to the most notorious frontier in the world, the North-West Frontier, which today forms the volatile boundary between Pakistan and Afghanistan. Known collectively as 'Henry Lawrence's young men', each had distinguished himself in the East India Company's wars in the Punjab before going on to make his name as a 'political' on the Frontier - Herbert Edwardes, who 'pacified' Bannu; John Nicholson, a forebear of the author who became the terror of the Sikhs as 'Nikkal Seyn'; 'Uncle' James Abbot of Hazara, and many others. Drawing extensively on their journals, diaries and letters, as well as his own recent travels in their footsteps, Charles Allen, acknowledged master story-teller of imperial history, weaves the individual stories of these soldier sahibs into an extraordinary tale that climaxes on Delhi Ridge in 1857, when the brotherhood came together to 'save' India